ANALISA EKONOMI POLITIK SEKTOR PERIKANAN TANGKAP DI INDONESIA - Agustino, Rinto (LP2M Universitas Bina Bangsa, 2025)
The fisheries sector in Indonesia has a strategic role in supporting the national economy while maintaining environmental sustainability. With a sea area of 6.4 million km² and the second longest coastline in the world, Indonesia has abundant fisheries potential. However, the dynamics of political economy involving policies, actors, and structural challenges often affect the effectiveness of the management of this sector. This article analyzes how political economy affects the fisheries sector in Indonesia, focusing on policies, conflicts of interest, and their impact on sustainability. The research method used is qualitative research with a descriptive approach. Qualitative research is a research method that explores and understands meaning in a number of individuals or groups of people that come from social or humanitarian problems. Qualitative research in general can be used for research on people's lives, history, behavior, concepts or phenomena, social problems, and others. The political economy of the fisheries sector in Indonesia reflects the complexity of resource management involving various actors and interests. Despite various challenges, the potential of this sector remains great if managed sustainably and inclusively. With the right policies and synergy between actors, the fisheries sector can become the main pillar in national economic development while preserving the environment